SYMBOL OF LIGHT IN VARIOUS RELIGIOUS TRADITIONS AND PHILOSOPHY (Journal of Philosophy, Culture and Political Science, 2024)
Light is a symbol of deep meaning in many philosophical traditions and cultures. Often the sacred is associated with light, and the worldly and profane with darkness. Light was not always easily accessible, and therefore sometimes had mystical significance for different societies. Later it began to be used as a symbol. In human nature, such a concept has historically been entrenched as an archetype. During primitive society, leaders, priests and warriors were associated with the Sun, the divine light. They could also differ in clothing or color on the face and body, clothing. Color has symbolic meaning for various cultures and peoples. Currently, some nations and religions have their own color tradition. Color associations are important in everyday life.The philosophy of Sufism also has a concept of light, darkness and color symbolism. In the works of Sufi philosophers one can find interpretations of various colors. In the tariqa of Kubrawiya there is a whole system of color sequence of the spiritual path. In addition, followers of tariqas can be distinguished by the shape and color scheme of everyday and ritual clothing.This article will examine the symbol of light in various religious traditions and philosophies, including the practice of light photisms of the Kubraviya tariqat.Key words: sacred light, light photisms, sufism, kubrawiya, color associations